Exploring psychological mechanisms of personalised advertising affecting online impulse buying in the social commerce context - Li, Kangying (2022)
Purpose - The purpose of this research is to investigate how perceived personalisation of social media advertising influences online impulse buying. In the context of social commerce, this study focused on the factors associated with advertising and their determinant roles in impulse buying. Using S-O-R as a theoretical basis, this research establishes a multi-step theoretical model incorporating Perceived ad personalisation, Perceived interactivity, Perceived involvement, and Arousal as predictors of impulse buying. Accordingly, this research seeks to disclose the mechanisms of multiple paths that could reveal the influence of the advertising’s psychological effects on consumers’ purchase intentions. Design/methodology/approach - This research is considered confirmatory in nature to extend the existing literature. The research paradigm of positivism is employed to conduct the project. The quantitative approach is therefore applicable to this study. Specifically, this research conducted an online survey using measurements adapted from the previous work. 313 valid responses were collected and used for the statistical analysis. Confirmatory factor analysis was employed to examine the reliability and validity of the measurement scales, followed by structural equation modelling to test the hypotheses. Findings - The results of data analysis indicated the predictive role of perceived ad personalisation on online impulse buying. Specifically, this research highlighted the indirect effect of Perceived ad personalisation on Urge to buy impulsively through Perceived involvement and Arousal. The findings confirmed the positive relationship between Perceived ad personalisation and Perceived interactivity, Perceived involvement and Arousal, respectively. In turn, Perceived involvement and Arousal positively related Urge to buy impulsively, whereas Perceived interactivity failed to pose a significant direct effect on the dependent variable. Further to this, it is thought that Perceived interactivity and Arousal may perform serial mediating effects that underlie the hypothesised psychological process as they were both shown to positively influence Perceived involvement. Originality/value - This research mainly contributes to incorporating the three intervening factors of Perceived interactivity, Perceived involvement and Arousal to the psychological mechanisms from Perceived ad personalisation to online impulse buying by extending the theoretical framework of S-O-R. This study also shed light on further studies pertinent in the context of social commerce, considering its empirical findings. Key words – social media advertising; online impulse buying; social commerce; perceived personalisation; perceived interactivity; perceived involvement; arousal.